Success and use factors of Malaysian public e-procurement system from the buyer perspective - Erne Suzila binti Kassim (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2011)
E-procurement in public administration is not an old phenomenon. Although its existence is just recent, two focal issues are significant to be investigated. First is the proven realization of its forecasted success. Second is the factors that influence the use that leads to the success. Therefore, the study was conducted to address the issues. Using the Malaysian public e-procurement system, known as ePerolehan as the context of the research, the use of the system was hypothesized to be significantly related with success measured as transparency, relationship development, service performance, information quality, process efficiency, cost efficiency and user satisfaction. Likewise, individual, organizational, environmental and technological factors were posited to influence the use of the ePerolehan system. The individual factors examined were user information system skills and knowledge, training and attitude. On the other hand, the organizational factors investigated were top management emphasis, organizational learning and facilitating condition. As for the environmental factors, the examined determinants were policy compliance, supplier expectation and mimetic pressure. Finally, the technological factors were information technology infrastructure, information technology risk and control and system compatibility. Besides, the mediating effect of dynamic capability on the relationship between organizational factors and use was also examined. The study was primarily conducted as a survey design among federal government agencies in Malaysia. Based on the analyses of 244 respondents, the findings suggest the use of the public e-procurement system has significant and positive influence to posited success. Moreover, the findings indicate significant relationships exist between individual factor, organizational factor, environmental factor, technological factor and e-procurement system use. In addition, there are also evidences of dynamic capability as a mediator to the organizational factor and system use relationship. Further analyses unveiled the significant success factors of the Malaysian public e-procurement system use, based on the level of strength are system compatibility, user attitude, organizational learning, IT infrastructure and supplier expectation. Therefore, it suggests for linkages between individual, organizational, environment and technological factors, and public e-procurement system use, at the organizational level. Such findings are imperative in providing evidences for a relationship between individual characteristics and system use for the organizations, which have not been proven before. The major theoretical contributions of the study include extending the previous literature on the success of information systems usage, verifying the linkage between individual factor and system use and validating the stability of organizational, environmental and technological factors in information system use by an organizational study. From the practical viewpoint, the findings have provided evidences for the Malaysian government e-procurement system success achievement. However, the study is subject to several limitations mainly on the success which should not be interpreted as an absolute procurement achievement since the responses gathered only from the buyer perspective. Hence, future efforts should be placed on examining the success from various contexts.